The Implementation of Gerakan Aisyiyah Sehat "GRASS" for Aisyiyah Cadres in West Kalimantan - Lidia Hastuti; Wuriani; Yenni Lukita; Ayu Rizky; Nuruniyah; Tilawati Aprina; Nurul Paramitha; M. Ikhwanudin Siswanto; Rizki Akbar Ramadhan (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Background: Cancer is one of the four main diseases in society which can attack all levels of society without exception and regardless of social status, age or gender. The number of breast cancer sufferers shows an increase every year. Secondary prevention is carried out through early detection of breast cancer, namely breast self-examination (BSE), which is a simple, cheap, non-invasive and harmless early detection program. In line with the above, Aisyiah in the health assembly program carries the Gerakan Aisyiyah sehat (GRASS). One of the GRASS programs is reproductive health which focuses on the BSE Movement for Aisyiyah cadres. The problem with partners is that Aisyiyah cadres spread across 14 districts/cities have never carried out education or training for new cadres related to SADARI, both increasing the knowledge and skills of cadres. For this reason, it is necessary to help partners, in this case the Aisyiyah Regional Leadership, to carry out SADARI campaigns and training to increase the knowledge and skills of cadres. Objective: This activity aims to increase cadres' knowledge and skills in BSE examinations. The focus of the service is conducting training on BSE for cadres in 14 districts/cities in West Kalimantan. Method: the activity is to carry out a BSE campaign and BSE training for Aisyiyah cadres in 14 regencies/cities in West Kalimantan province. Results: From the activity evaluation, the results showed that the average knowledge score was 84.46 and the average skills score in the BSE examination was 82.97. Conclusion: SADARI campaigns and training increase the knowledge and skills of Aisyiyah cadres.